Thermophysical and electrical properties of rare‐earth‐cerate high‐entropy ceramics. Issue 7 (10th April 2022) - Ping, Xinyu; Meng, Bin; Li, Chen; Lin, Wu; Chen, YingQuan; Fang, CongCong; Zhang, Han; Liang, Wenke; Zheng, Qian
Abstract: A new series of rare‐earth‐cerate high‐entropy ceramics with compositions of (La0.2 Nd0.2 Sm0.2 Gd0.2 Dy0.2 )2 Ce2 O7 (HEC1), (La0.2 Nd0.2 Sm0.2 Gd0.2 Yb0.2 )2 Ce2 O7 (HEC2), (La0.2 Nd0.2 Sm0.2 Yb0.2 Dy0.2 )2 Ce2 O7 (HEC3), (La0.2 Nd0.2 Yb0.2 Gd0.2 Dy0.2 )2 Ce2 O7 (HEC4), (La0.2 Yb0.2 Sm0.2 Gd0.2 Dy0.2 )2 Ce2 O7 (HEC5) as well as a single component of Nd2 Ce2 O7 are fabricated via sintering the corresponding sol–gel‐derived powders at 1600°C for 10 h. HEC1–5 samples exhibit a single‐cerate phase with fluorite structure and high configurational entropy. Compared with Nd2 Ce2 O7, HEC1–5 samples have a lower grain growth rate owing to the sluggish diffusion effect. The chemical compositional uniformity of HEC1–5 as well as Nd2 Ce2 O7 does not apparently change after annealing at 1500°C for different time intervals (1, 6, 12, and 18 h). Compared with 8YSZ, HEC1–5 samples display the decreased thermal conductivity and increased thermal expansion coefficient. The lattice size disorder parameter of HEC1–5 is negatively related to the thermal conductivity in 26–450°C. Furthermore, HEC1–5 and Nd2 Ce2 O7 exhibit lower oxygen‐ion conductivity, meaning an increased resistance to oxygen diffusion.